Creating Innovators in Mobile Application Development. The Experience of Apps.co in Santander - Lizcano, Adriana Rocío; Arévalo, Armando; Zabala, Sergio Andrés (Ingeniería Solidaria, 2014)
Apps.co is an initiative of the Ministry of Information Technology and Communication (MinTIC) and its Vive Digital (Live Digital) plan for promoting, through the use of information and communication technology (ICT), the creation of businesses that focus on developing mobile applications, software and content. The government’s goal is to generate at least 400 solutions in international markets. The Apps.co program consists of four phases: Bootcamps, Conceptualization, Prototyping and Validation, Acceleration and Consolidation. The National Government involved strategic allies to execute this process. In Conceptualization, Prototyping and Validation, Santander has: 1. Apps.co UNAB and 2. Santander Apps  (a joint venture between UPB, UDI and CETICS). Each of these has coordinated 20 startups per iteration, providing technical and business consulting over an eight-month support period to consolidate the idea and the business model, and create a prototype of the application. This article summarizes the methodological and technical aspects of work done by the Santander Apps alliance in the “Conceptualization, Prototyping and Validation” phases. The article finishes with a description of the results and lessons learnt in order to create a knowledge base that can be used by different players in the economy and the national education system for technology entrepreneurship processes.
Keywords: application development; ICT entrepreneurship; lean launch pad; Ministry of ICT